Knowledge on the risk factors of drug-resistant tuberculosis among newly diagnosed patients of tuberculosis with first-line antitubercular treatment regimen - Rajsinh Vishwasrao Mohite (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The emergence of multidrug-resistant tuberculosis (MDR-TB), a new public health challenge, acts as an obstacle to the national TB elimination program in India. OBJECTIVES: The objective of the study was to assess knowledge on risk factors of drug-resistant (DR) TB and to determine its association with sociodemographic factors among newly diagnosed patients of TB. MATERIALS AND METHODS: A cross-sectional study was carried out in the year 2019 among 425 adult TB patients on first-line anti-TB treatment from District TB Centre Satara, India. A structured interview was employed to collect information on the knowledge variables of risk factors associated with DR-TB. RESULTS: Maximum 58.3% belonged to the age group from 15 to 34 years with a higher proportion of 63.5% belonging to males. Maximum 66.8%, 59.2%, and 46.1% of patients felt that defaulter, poor treatment compliance, and delay in the initiation of anti-TB treatment as risk factors for the emergence of drug resistance TB (DR-TB), respectively. Behavioral risk factors such as alcohol and tobacco exposure were also felt as risk factors by maximum 64%, and 59.7% of patients, respectively. Based on the knowledge category, maximum 46.5% of participants belonged to the poor; however, only 16.7% fall in the good category. Age, education, occupation, income, and residence were significantly associated with knowledge on the possible risk factors of DR-TB among participants (P < 0.05). CONCLUSION: The study has elicited overall poor knowledge on the risk factors of DR-TB. Health empowerment of family and community with effective health education strategy may reduce the problem of the emergence of DR-TB.